HUBUNGAN INTENSITAS PENGGUNAAN GADGET DENGAN KELUHAN COMPUTER VISION SYNDROME PADA SISWA-SISWI DI SMPN 4 DENPASAR - I Gst Ag Istri Agung Gayatri; Luh Mira Puspita; Ni Kadek Ayu Suarningsih (Coping: Community of Publishing in Nursing, 2020)
Teenagers are known to be the most gadget users today. Most of them have the intensity of using gadgets for approximately 5 hours and would be increasing. Excessive use of gadgets can lead to Computer Vision Syndrome (CVS) such as fatigue and eye disorders. This study aims to determine the relationship between intensity of gadget’s use with CVS complaints on students of Junior High School 4th Denpasar. The method in this study is cross-sectional by using questionnaires as data instrument. This study used simple random sampling as sampling technique and determined 179 students as the sample. The results showed that almost half of the respondents had the intensity of using gadgets in the low category (43%) and the most respondents had CVS complaints in the medium category (39%). There is a relationship between the intensity of gadget usage with CVS complaints (p value = 0.05; a = 0.05; r = 0.086). The relationship is weakly positive which indicates that the higher intensity of use of gadgets would lead the higher CVS complaints felt by students.